How Can a Marketing Strategy Enhance the Competitiveness of Calligraphy MSMEs? - Hasan, Muhammad; Arisah, Nur; Nurdiana, Nurdiana; Ahmad, Muhammad Ihsan Said; Riesso, Andi Sawe (Universitas Pendidikan Ganesha, 2024)
The development of Indonesian MSMEs is currently relatively fast, causing competition among MSMEs. The competition among MSMEs currently requires MSMEs to increase their business competitiveness, so they have sufficient potential to continue to compete with other MSMEs. MSMEs are still faced with the low ability to determine their marketing strategy so it is considered as one of the causes of the low competitiveness of MSMEs. This study aims to determine and reveal the role of marketing strategies on the competitiveness of MSMEs. This research is categorized as quantitative research with correlational research design. This research was conducted on 30 Calligraphy MSMEs located in Semarang Regency, Central Java the research subject being 30 Calligraphy MSME owners who were directly involved in the management and operation of the business. The data collection technique used is a questionnaire. The data analysis method used was SEM analysis. The findings of this study indicate that marketing strategies play a positive role in increasing the competitiveness of calligraphy MSMEs in Semarang Regency, Central Java Province. These findings have implications for the need of Calligraphy SMEs to be able to continue to develop their marketing through the current digital platform because this marketing strategy will be able to help the promotion process and provide value to the consumers.